2014
DOI: 10.1021/cb500063y
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Sculpting of Ligand-GPCR Subtype Selectivity: The Case of Angiotensin II

Abstract: GPCR subtypes possess distinct functional and pharmacological profiles, and thus development of subtype-selective ligands has immense therapeutic potential. This is especially the case for the angiotensin receptor subtypes AT1R and AT2R, where a functional negative control has been described and AT2R activation highlighted as an important cancer drug target. We describe a strategy to fine-tune ligand selectivity for the AT2R/AT1R subtypes through electronic control of ligand aromatic-prolyl interactions. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…31 This novel AT2R agonist, bearing the peptide sequence DRVYIYPF, significantly stimulates neurite outgrowth in AT2R over-expressing PC12W rat pheochromocytoma cell line, in a dose-dependent manner. 31 In the same study we pinpointed that this compound served as a negative regulator of AT1R signaling since it was able to inhibit MCF-7 breast carcinoma cellular proliferation in the low nanomolar range. 31 These results suggested that this novel AT2R agonist binds selectively to the AT2R and its biological activity is equally strong as an endogenous ligand Ang II.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…31 This novel AT2R agonist, bearing the peptide sequence DRVYIYPF, significantly stimulates neurite outgrowth in AT2R over-expressing PC12W rat pheochromocytoma cell line, in a dose-dependent manner. 31 In the same study we pinpointed that this compound served as a negative regulator of AT1R signaling since it was able to inhibit MCF-7 breast carcinoma cellular proliferation in the low nanomolar range. 31 These results suggested that this novel AT2R agonist binds selectively to the AT2R and its biological activity is equally strong as an endogenous ligand Ang II.…”
Section: Introductionmentioning
confidence: 89%
“…31 In the same study we pinpointed that this compound served as a negative regulator of AT1R signaling since it was able to inhibit MCF-7 breast carcinoma cellular proliferation in the low nanomolar range. 31 These results suggested that this novel AT2R agonist binds selectively to the AT2R and its biological activity is equally strong as an endogenous ligand Ang II. Therefore, this novel AT2R agonist can serve as a valuable compound for AT2R-targeted stimulation and may control pathological conditions associated with Ang IIreceptor signaling, such as hypertension, coronary artery disease, kidney disease and various cancers.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Establishing ligands that will present enhanced selectivity for AT 2 R vs. AT 1 R is based on the fact that AT 2 R antagonizes the functions of AT 1 R. Activation of AT 2 R leads to apoptosis, antiproliferation and vasodilation, whereas activation of AT 1 R leads to cellular growth, proliferation and vasoconstriction 40 . Wan et al, synthesized the first selective nonpeptide AT 2 R agonist M024/C21 (Fig.…”
Section: Fig 11: the Compounds With Dual At 1 R Antagonism And Pparγmentioning
confidence: 99%